ANALISIS KESULITAN BELAJAR MATEMATIKA DALAM PENULISAN BILANGAN PANJANG SISWA KELAS III MADRASAH IBTIDAIYAH NURUL IHSAN BALERAJA, GANTAR, INDRAMAYU - Siti Nur Afifah; kartini kartini; Alfi Satria (JOEL: Journal of Educational and Language Research, 2022)
This thesis examines about the difficulties of learning mathematics in the writing of the numbers the length of the third grade students of MI Nurul Ihsan Baleraja. The principal problem which is first of this research is the students difficulties in writing numbers long in mathematics, the difficulty of the placement of the numbers starting from thousands, hundreds, tens, and units. The principal problem of the second what are the difficulties of learning mathematics in the writing of the numbers the length of the third grade students of MI Nurul Ihsan Baleraja, and the principal problem is how to overcome the difficulties of learning mathematics in the writing of the numbers the length of the students of class III MI Nuru Ihsan Baleraja. The purpose of this research is to know the difficulties of learning mathematics in the writing of the numbers the length of the third grade students of MI Nurul Ihsan Baleraja and to find out how to overcome the difficulties of learning mathematics in the writing of the numbers the length of the third grade students of MI Nurul Ihsan Baleraja. This research method uses a qualitative descriptive approach with the techniques of observation, interview, and documentation in depth to teachers and students of MI Nurul Ihsan Baleraja, the city of indramayu, academic year 2021/2022 The results showed that there are difficulties learning mathematics in a number of writing the length of the third grade students of MI Nurul Ihsan Baleraja, it can be k: learning difficulties is the inability of students in mastering the concepts, principles, facts and skills, the factor of self and the factors that come from outside the child makes the child is difficult in following the learning process whether it is the reception, the process, the information conveyed by the teacher during the learning in the classroom, the Efforts that can be done to reduce the difficulty of learnin2g that teach math with fun as well using methods that make the child spirit in learning mathematics, reproduce exercise, and establish cooperation between parents of students.